2015
DOI: 10.1080/2162402x.2015.1091555
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the first-in-class T-cell-engaging bispecific single-chain antibody for targeted immunotherapy of solid tumors expressing the oncofetal protein claudin 6

Abstract: The fetal tight junction molecule claudin 6 (CLDN6) is virtually absent from any normal tissue, whereas it is aberrantly and frequently expressed in various cancers of high medical need.We engineered 6PHU3, a T-cell-engaging bispecific single chain molecule (bi-(scFv)2) with anti-CD3/anti-CLDN6 specificities, and characterized its pharmacodynamic properties.Our data show that upon engagement by 6PHU3, T cells strongly upregulate cytotoxicity and activation markers, proliferate and acquire an effector phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Both MV and VSV are clinically developed for virotherapeutic purposes against different tumor entities including ovarian carcinoma, which also reveal significant up-regulation of CLDN6 23 , 47 , and thus constitutes an ideal tumor vaccination target, too, since few auto-immunity is to be anticipated. Indeed, passive immunotherapy with anti-CLDN6 mAb (IMAB027) is currently under clinical development for patients with recurrent advanced ovarian cancer (NCT02054351).…”
Section: Discussionmentioning
confidence: 99%
“…Both MV and VSV are clinically developed for virotherapeutic purposes against different tumor entities including ovarian carcinoma, which also reveal significant up-regulation of CLDN6 23 , 47 , and thus constitutes an ideal tumor vaccination target, too, since few auto-immunity is to be anticipated. Indeed, passive immunotherapy with anti-CLDN6 mAb (IMAB027) is currently under clinical development for patients with recurrent advanced ovarian cancer (NCT02054351).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the T EM cell population expanded during treatment of ALL patients with blinatumomab, and T EM expansion was also shown in long term T cell cultures expanded with BiTE ESK-1 (31, 32). Treatment with 6PHU3, a BiTE that targets claudin 6, was also found to increase the population of T EM in the tumors of xenografted mice (33). The T EM cell population has also been shown to contribute to BiTE redirected target cell lysis.…”
Section: Discussionmentioning
confidence: 97%
“…Determining the complex structures of other CLDNs and anti‐CLDN antibodies with proven pharmaceutical utility will promote theoretical in silico drug design for CLDN‐targeted drug development. In addition, clinical trials of anti‐CLDN antibodies as antitumor reagents are ongoing, and several groups are developing and screening new types of CLDN binders …”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition, clinical trials of anti-CLDN antibodies as antitumor reagents are ongoing, and several groups are developing and screening new types of CLDN binders. [88][89][90][91] Acknowledgments This work was supported by a Health and Labour Sciences Research grant from the Ministry of Health, Labour, and Welfare of Japan; a grant-in-aid for Scientific Research from the Ministry of Education, Culture, Sports, Science, and Technology of Japan (24390042); a grant from the Adaptable and Seamless Technology Transfer Program through targetdriven R&D, Japan Science and Technology Agency; a grant from the platform for drug discovery, informatics, and structural life science of the Ministry of Education, Culture, Sports, Science, and Technology, Japan; a grant from the Japan Agency for Medical Research and Development; and the Takeda Science Foundation. Y.H.…”
Section: Future Perspectivesmentioning
confidence: 99%